The Hail Phenomenon in Qs. An-Nur/24:43 (A Comparative Study of the Interpretations of Fakhruddin al-Razi and Zaghlul Al-Najjar) - Ihwan Amalih; Arifatul Lailiyah (Penerbit Hellow Pustaka, 2026)
This article examines the phenomenon of hail in QS. An-Nur/24:43. In the Qur'an, there is only one verse that discusses this phenomenon. This article reviews the thoughts of both a classical and a contemporary exegete, namely the interpretations of Fakhruddin al-Razi and Zaghlul Al-Najjar. Fakhruddin al-Razi’s interpretation has a diverse approach, including rational, theological, philosophical, legal, and fiqhi perspectives. Meanwhile, Zaghlul Al-Najjar’s interpretation follows a scientific approach. This article employs a qualitative method using a library research. It discusses the interpretations of Fakhruddin al-Razi and Zaghlul Al-Najjar regarding the phenomenon of hail in QS. An-Nur/24:43, as well as the similarities and differences between these two exegetes on this phenomenon. The research findings conclude that Fakhruddin al-Razi only explains the formation of clouds through water vapor but does not elaborate on the process of cumulus cloud formation that leads to hail. In contrast, Zaghlul Al-Najjar describes the process of cloud formation through water vapor, the growth of cumulus clouds, the formation of ice within these clouds, and the role of ice in the occurrence of lightning. There is a difference in writing methods and depth of explanation, as Fakhruddin al-Razi uses the tahlili (analytical) method, while Zaghlul Al-Najjar applies the maudhu’i (thematic) approach, focusing solely on scientific verses (ayat kauniyah). However, both exegetes share a key similarity in affirming the scientific miracles of the Qur'an, employing a scientific approach, and integrating Qur’anic science with modern scientific developments.